The impact of natural resource rents on environmental degradation in case of USA: The role of technological innovation and renewable energy consumption - Sarosh, Sarah; Yen, Chang Mei (Asian Journal of Economics and Empirical Research, 2024)
This study explores the impact of natural resource rents on CO2 emissions in the presence of renewable energy consumption, technological innovation, and gross domestic product (GDP) in the case of the USA from 1990 to 2020. For sustainable development policies and to slow down environmental degradation, it is important to understand the intricate connection between resource rents and carbon emissions in the US. Thus, this study hypothesizes that after controlling for renewable energy consumption, technological innovation, and GDP, among other variables, resource rents significantly contribute to carbon dioxide emissions in America. This study adds significantly to the existing literature on how resource rents affect CO2 emissions in the United States. This study employs quantile regression estimation techniques, which provide vital policy insights and academic contributions that are relevant to sustainable development and environmental conservation from both national and global perspectives. The results show that natural resource rents (NNRs) and GDP are positively associated with CO2 emissions at all quantiles. Moreover, the results indicate that technological innovation and renewable energy consumption are important in curbing CO2 emissions.